Comparison of models for missing pedigree in single-step genomic prediction. (25th January 2021) - Masuda, Yutaka; Tsuruta, Shogo; Bermann, Matias; Bradford, Heather L; Misztal, Ignacy
Abstract: Pedigree information is often missing for some animals in a breeding program. Unknown-parent groups (UPGs) are assigned to the missing parents to avoid biased genetic evaluations. Although the use of UPGs is well established for the pedigree model, it is unclear how UPGs are integrated into the inverse of the unified relationship matrix (H-inverse) required for single-step genomic best linear unbiased prediction. A generalization of the UPG model is the metafounder (MF) model. The objectives of this study were to derive 3 H-inverses and to compare genetic trends among models with UPG and MF H-inverses using a simulated purebred population. All inverses were derived using the joint density function of the random breeding values and genetic groups. The breeding values of genotyped animals (u 2 ) were assumed to be adjusted for UPG effects (g ) using matrix Q 2 as u 2 ∗ = u 2 + Q 2 g before incorporating genomic information. The Quaas–Pollak-transformed (QP) H-inverse was derived using a joint density function of u 2 ∗ and g updated with genomic information and assuming nonzero c o v ( u 2 ∗, g ′ ) . The modified QP (altered) H-inverse also assumes that the genomic information updates u 2 ∗ and g, but c o v ( u 2 ∗, g ′ ) = 0 . The UPG-encapsulated (EUPG) H-inverse assumed genomic information updates the distribution of u 2 ∗ . The EUPG H-inverse had the same structure as the MF H-inverse. Fifty percent of the genotyped females in the simulation had a missing dam, and missing parents were replaced with UPGs by generation. The simulation study indicated that u 2 ∗ and g in models using the QP and altered H-inverses may be inseparable leading to potential biases in genetic trends. Models using the EUPG and MF H-inverses showed no genetic trend biases. These 2 H-inverses yielded the same genomic EBV (GEBV). The predictive ability and inflation of GEBVs from young genotyped animals were nearly identical among models using the QP, altered, EUPG, and MF H-inverses. Although the choice of H-inverse in real applications with enough data may not result in biased genetic trends, the EUPG and MF H-inverses are to be preferred because of theoretical justification and possibility to reduce biases.